Ragam Larutan Mikroorganisme Lokal Sebagai Dekomposter Rumput Gajah (Pennisetum purpureum) - Nurul Puspita Palupi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2015)
Objectives of the research were: (1) To study the process of making mol from fresh ingredients; and (2) To determine the effect of mol resulted on the making of elephant grass Bokashi.Research conducted on 12 February 2015 up to 16 April 2015 in the OECF Building of the Faculty of Agriculture, Mulawarman University. It included: preparation, making of mol from water hyacinth, making of elephant grass Bokashi and data collection. The research results revealed that: (1) The effect of different moles solution provided different success of elephant grass bokashi due to different fresh material used by each group; and (2) The results when sorted from the best to the worst were fish waste, papaya peels, banana peels, pineapple peels, cabbage waste, water hyacinth, and lamtoro.